Multimodal analgesia for laparoscopic operations in gynecology - Khalimonchyk, Victoriia; Klygunenko, Olena (ScienceRise: Medical Science, 2019)
Adequate postoperative pain relief is an integral part of anesthesia management. Postsurgical pain can be treated effectively with both strong analgesics and prevention of central sensitization. Objective: to evaluate the antinociceptive effect of the combined intraoperative use of ketamine and dexketoprofenafter elective laparoscopic gynecological surgery. Materials and methods: 80 females undergoing laparoscopic gynecological surgery with total intravenous anesthesia (TIVA) with propofol and fentanyl. Patients were randomly assigned into three groups depending on multimodal analgesia choice, matched by age, and the nature of surgical intervention. Demographic characteristics, anthropometric data, functional status, duration of surgery and anesthesia were similar in all groups. Group I patients (n=30) received TIVA with mechanical ventilation. Group II patients (n=25) received TIVAwith additional administration of subanesthetic doses of ketamine. Group III patients (n=25) received TIVA with additional administration of subanesthetic doses of ketamine and a single administration of 50 mg of dexketoprofen 30 minutes before the end of the surgery. The intensity of postoperative pain was evaluated by VAS at 1, 2, 6, 12 and 24 hours after surgery. Time of the first analgesic administration and the incidence of side effects were recorded. Results: Estimates of the intensity of pain according to VAS at rest and on movement during the first 12 hours after surgery were significantly higher in group I compared with groups II and III (p<0.05). 1 hour after surgery the level of pain at rest and on movement was significantly higher in group II patients than in group III. The need for additional administration of analgesics after surgery was 53.3 % for Group I, 40 % for Group II, and 28 % for Group III. Conclusions: Traditional general anesthesia (TIVA with propofol and fentanyl with mechanical ventilation) does not prevent moderate to severe postoperative pain in most patients. Intraoperative use of subanesthetic doses of ketamine reduces postoperative pain in early stages after laparoscopic gynecological surgery. Combined intraoperative use of low doses of ketamine (up to 0,5 mg/kg) and dexketoprofen (50 mg) provides the most effective analgesia during the first 12 hours after laparoscopic gynecological surgery, delays first injection of analgesics and reduces need for additional analgesics prescription